2014
DOI: 10.1167/iovs.14-14872
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Adult Stem Cells in Schwalbe's Line Region of the Primate Eye

Abstract: We provide evidence for a niche in the Schwalbe's line region harboring cells with long-term BrdU retention and OCT4 immunoreactivity. The cells likely constitute a population of adult stem cells with the capability to compensate for the loss of TM and/or corneal endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 53 publications
1
31
0
1
Order By: Relevance
“…The newly derived TM cells are derived from a population of progenitor cells located directly beneath the Schwalbe's line that are suspected to resemble stem cells (48). It is intriguing to speculate whether the endogenous TM cells re-entering the cell cycle following iPSC-TM transplantation belong to this particular TM cell subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The newly derived TM cells are derived from a population of progenitor cells located directly beneath the Schwalbe's line that are suspected to resemble stem cells (48). It is intriguing to speculate whether the endogenous TM cells re-entering the cell cycle following iPSC-TM transplantation belong to this particular TM cell subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Braunger et al 50 identified stem cells in the anterior chamber angle of the monkey eyes by detecting BrdU longterm retention. They treated 4 monkeys with BrdU for 4 weeks and found that the number of BrdU-positive cells was higher at Schwalbe's line covering the peripheral end of Descemet's membrane than in regions of JCT, TM, and scleral spur.…”
Section: Label-retaining Assaysmentioning
confidence: 99%
“…Adult stem cells have also been identified in the region of Schwalbe's line adjacent to Descemet's membrane in primate eyes. These cells retained BrdU and displayed OCT 4 immunoreactivity [57]. A similar region was observed in human TM by Acott et alwho found 4-fold replication of cells in the anterior TM adjacent to Schwalbe's line after treatment with laser trabeculoplasty [58].…”
Section: Introductionmentioning
confidence: 73%